An intelligent system for pavement management - Brega, JRF; Soria, MHA; Marar, João Fernando [UNESP]; Sementille, Antonio Carlos [UNESP] (Spie - Int Soc Optical Engineering, 1998)
This paper describes a method for the evaluation of pavement condition through artificial neural networks using the MLP backpropagation technique. Two of the most used procedures for detecting the pavement conditions were applied: the overall severity index and the irregularity index. Tests with the model demonstrated that the simulation with the neural network gives better results than the procedures recommended by the highway officials. This network may also be applied for the construction of a graphic computer environment.
Keywords: intelligent system; artificial neural networks; pavement management system